2020
DOI: 10.19113/sdufenbed.631074
|View full text |Cite
|
Sign up to set email alerts
|

Hyoscyamus reticulatus L. Tohum Ekstraktının Antimikrobiyal ve Apoptotik Etkinliğinin Araştırılması

Abstract: Özet: Hyoscyamus reticulatus Solanacea ailesindendir ve ülkemizde altı türü bulunmaktadır. Hyoscyamus türleri özellikle halk arasında yaygın olarak kullanılan skopolamin ve hiyosiyamin gibi tropan alkaloitleri kaynağıdır. H. reticulatus tohumundan soxhlet yöntemi ile elde edilen etil alkol ekstresinin bazı Gram (-) ve Gram (+) bakteri ve mayalara karşı antimikrobiyal aktivitesinin tespit edilmesi ve H. reticulatus tohumunun plazma ve beyin numunelerinde TP53 ve Bcl-2 seviyeleri ölçülerek apoptotik etkisinin be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…It showed growth inhibition zone diameters of 14, 15, 14, and 20 mm against these pathogens, respectively (Mateen et al, 2015). It has been reported that H. reticulatus seed extract has an antimicrobial effect against Bacillus subtilis, Escherichia coli, Klebsiella pneumoniae, Pasteurella multicoda, Pseudomonas aeruginosa, Salmonella enteritidis, Staphylococcus aureus, Yersinia enterocolitica microorganisms (Akbaş et al, 2020). It has been determined that the leaf parts of give have a significant antimicrobial effect (Hossain et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It showed growth inhibition zone diameters of 14, 15, 14, and 20 mm against these pathogens, respectively (Mateen et al, 2015). It has been reported that H. reticulatus seed extract has an antimicrobial effect against Bacillus subtilis, Escherichia coli, Klebsiella pneumoniae, Pasteurella multicoda, Pseudomonas aeruginosa, Salmonella enteritidis, Staphylococcus aureus, Yersinia enterocolitica microorganisms (Akbaş et al, 2020). It has been determined that the leaf parts of give have a significant antimicrobial effect (Hossain et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…When the antimicrobial results of H. niger are compared with the literature studies, it is seen that the results obtained are different from each other. Alkaloids, glycosides, flavonoids, and their derivatives, which are usually found in plant extracts, are responsible for the antimicrobial effect (Dulger et al, 2010a-b; Benhouda et al, 2014; Dulger and Dulger, 2015; Ayari-Guentri et al, 2017; Elsharkawy et al, 2018; Akbaş et al, 2020). In addition, the plant species, concentrations, and microorganisms used to affect the antimicrobial results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations